2011
DOI: 10.5005/jp-journals-10005-1086
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Gingival Fibromatosis

Abstract: Idiopathic gingival fibromatosis is a rare heriditary condition characterized by slowly progressive, nonhemorrhagic, fibrous enlargement of maxillary and mandibular keratinized gingiva caused by increase in submucosal connective tissue elements. This case report gives an overview of gingival fibromatosis in a 11-year-old female patient who presented with generalized gingival enlargement. Based on the history and clinical examination, the diagnosis was made and the enlarged tissue was surgically removed. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…HGF is a highly unusual condition characterized by a benign gingival overgrowth. It is inherited in an autosomal-dominant or, less frequently, autosomal-recessive manner [ 10 , 11 ]. Autosomal-dominant non-syndromic forms of HGF acquired by inheritance are associated with the chromosomes 2p21-p22 and 5q13-q22 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…HGF is a highly unusual condition characterized by a benign gingival overgrowth. It is inherited in an autosomal-dominant or, less frequently, autosomal-recessive manner [ 10 , 11 ]. Autosomal-dominant non-syndromic forms of HGF acquired by inheritance are associated with the chromosomes 2p21-p22 and 5q13-q22 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gingival fibromatosis is an infrequent, benign condition that can be cropped up as an isolated disease, chromosomal abnormality, or can be associated with the syndromes. 11 It may be congenital or hereditary. 1 The pathogenesis behind the gingival fibromatosis is still not known but it has been observed that increased synthesis of collagen and proliferation of gingival fibroblast may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…For the removal of gingival fibromatosis, surgical intervention in form of a gingivectomy is carried out either in a conventional form, electrocautery, or with laser but the most efficacious treatment is conventional gingivectomy. 11 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Studies reveal an autosomal dominant inheritance with chromosomal abnormality in 2p21-p22 and 5q13-q22 [1, 4]. It could arise due to nutritional and hormonal factors [5].…”
Section: Discussionmentioning
confidence: 99%
“…It affects interdental papillae and marginal and attached gingiva unlike drug induced enlargement in which attached gingiva is uninvolved. The severity may vary from mild involvement of one quadrant to severe involvement of all four quadrants [4]. The enlarged tissues can partially or totally cover the crowns, cause diastemas and pseudopockets, delay tooth eruption, and cause malocclusion.…”
Section: Discussionmentioning
confidence: 99%